A versatile 2A peptide-based strategy for ectopic expression and endogenous gene tagging in Trypanosoma cruzi - Niemirowicz, Gabriela Teresa (2024)
Nearly all expression vectors currently available for Trypanosoma cruzi were conceived to produce a single primary transcript containing the genes of interest along with those that confer antibiotic resistance. However, since each messenger RNA (mRNA) matures separately, drug selection will only guarantee the expression of those derived from the selectable marker. Therefore, commonly a considerable fraction of the cells recovered after selection with these expression vectors, although resistant do not express the protein of interest. Consequently, in order to counteract this disadvantage, we developed vectors with an alternative arrangement in which the gene of interest and antibiotic resistance are fused sharing the same mRNA. To test this configuration, we included the coding sequence for the green fluorescent protein (mEGFP) linked to the one conferring neomycin resistance (Neo). Additionally, to allow for the production of two independent proteins the sequence for a Thosea asigna virus self-cleaving 2A peptide (T2A) was inserted in-between. Cells obtained with these vectors displayed higher mEGFP expression levels with more homogeneous transgenic parasite populations than those transfected with more conventional independent mRNA-based alternatives. Moreover, as determined by Western blot, 2A mediated fusion protein dissociation occurred with high efficiency in all parasite stages. In addition, these vectors could easily be transformed into endogenous tagging constructs that allowed the insertion, by ends-in homologous recombination, of a hemagglutinin tag (HA) fused to the actin gene. The use of 2A self-cleaving peptides in the context of single mRNA vectors represents an interesting strategy capable of improving ectopic transgene expression in T. cruzi as well as providing a simple alternative to more sophisticated methods, such as the one based on CRISPR/Cas9, for the endogenous labeling of genes.